Trans-border kitchens: Iberian recipes in seventeenth-century English manuscripts. Issue 1 (2nd January 2019) - Tigner, Amy L.
ABSTRACT: In this essay, I look at a particular set of seventeenth-century English manuscripts that include culinary, medicinal, or household recipes with Iberian origins: the Granville Family Recipe Book; Lady Ann Fanshawe's Recipe Book; Sarah Hughes ' Libro: Recetas de Portugal para hacer Peuetes y Pastillas y adreçar Guantes perfumados' ; and a section from the journals of Edward Montegue, 1 st Earl of Sandwich. These manuscripts that contain what I am calling 'trans-border' recipes provide a glimpse into the political, cultural and colonial history that illuminates the relationship between the Iberian Peninsula, England and the expanding globe. This history of food distribution is not one that reveals the decisions of highest levels of state, but rather it is a domestic history that nonetheless drove Europe's desire for new tastes and resources. As these trans-border recipes travel from Iberia to England – or, sometimes from the New World, Africa or Asia to Spain or Portugal and then to England – they also reveal the transmission of kitchen techniques, household practice, medical knowledge and culinary tastes. Trans-border recipes work to transform the bodies upon which act, so that the Iberian culinary, medicinal and cosmetic recipes are literally absorbed into English bodies, changing cultural expectations and physical circumstances.